Prospects of Community Service Criminal Policy as an Alternative to Imprisonment in Indonesia: A Comparative Study Between Countries - Ramadhani, Rahmania; Wijayanto, Indung (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: This article analyzes the comparative policies of social work sentences in Indonesia and other countries, as well as the prospects for social work sentences as an alternative to imprisonment in Indonesia.Purposes of the Research: This study aims to provide prospective ideas regarding the policy of social work as an alternative to imprisonment in Indonesia and to compare it with policies in other countries, such as the Netherlands, England, and Malaysia.Methods of the Research: This study uses normative legal methods with a comparative and legislative approach. The legal materials used include primary and secondary legal materials, which are collected through literature studies.Findings of the Research: The results of the study found that although social work has been regulated in Law Number 1 of 2023, its regulation is still limited and faces various institutional and social challenges. Compared to other countries that are more mature in their implementation, Indonesia is still in the early stages of development. However, the prospects are considered promising because they can reduce overcrowding, suppress recidivism, and provide social benefits. Therefore, it is recommended that the government immediately draft implementing regulations, strengthen the capacity of related institutions, build multi-sector collaboration, conduct public outreach, and carry out further evaluations and research.